Cognitive and Metacognitive Reading Strategies for Ethiopian Students in English as a Foreign Language - Madebo, Deneke; Gutema, Hailu (Educational Challenges, 2024)
Purpose. This study's purpose is to investigate the effects of explicit cognitive reading strategy training on reading performance and metacognitive reading strategy awareness of Grade 9 students of Heto Secondary School at Hosanna Town, 232, south-west of Addis Ababa. Methodology. For this quasi-experimental study, two parallel home-made tests, a pre-test and a post-test administered before and after the intervention, respectively, and a metacognitive reading strategy awareness questionnaire were used. Data were gathered from 100 participants of experimental and control groups, 50 students from each group, before and after 14 hours strategy training within 12 weeks. SPSS, version 25, was used to analyse data. Independent Samples Test to compare groups, and Paired Samples Test to compare variables/scores of the groups were employed during analysis. Results. The results showed a statistically significant difference between the pre-test and the post-test scores of reading performance (p=.000) of each group. However, the Experimental Group made an increment in reading performance, whereas the Control Group made the opposite, a decrement in reading performance. The relationship of both groups was strong and positive. However, neither group showed significant changes in metacognitive reading strategy awareness. Conclusion. The study concluded that explicit cognitive reading strategy instruction empowered students to outperform reading comprehension and vice versa, though it did not change students’ strategy awareness. This implies that concerned bodies should give due attention to enhancing the explicit approach to cognitive reading strategy teaching.
Keywords: cognitive reading strategy; explicit strategy training; metacognitive reading strategy awareness; reading performance